Repatriation of Rwandan Returnees In Kigali: Integration of those Born and Raised on Exile as a Result of the 1959 Violence Wave - Sanchez, Cristina Taulet; College, Davidson (Independent Study Project (ISP) Collection, 2018)
This study explores the repatriation process of millions of Rwandans that returned to Kigali after the 1994 genocide against the Tutsi, focusing on those that were born and raised in Uganda, Democratic Republic of Congo, Tanzania, and Burundi as a result of the ethnic violence in 1959 and its aftermath. To complete this project, both theoretical and empirical research was conducted, including academic perspectives, numerical data analysis, and one-on-one interviews on the field. By examining the previous living conditions in the host countries, alongside the process of return and resettlement once in Rwanda, this study presents the physical and emotional integration of a young generation of Rwandans that returned their country of origin in which they had never resided.